Family-related life events: Insights from two Australian longitudinal studies - Baxter, J.A.; Moloney, L; Qu, L; Hayes, A; Baxter, Jennifer; Weston, R (Australian Institute of Family Studies, 2012)
The report examines the prevalence of different life events among Australian adults, and the links between life events, personal and family characteristics, and personal wellbeing. Life events include such things as family formation or separation, serious illness or bereavement, financial or employment change, or moving house. The report presents insights from two large-scale national longitudinal datasets: the Household, Income and Labour Dynamics in Australia (HILDA) Survey - which provides a broad population view - and Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) - which focuses exclusively on families with young children.
AIFS Research Report
Keywords: Families; Life Events -- Impact; Health -- Wellbeing; Disadvantage, adversity and resilience; Health and wellbeing; Families and relationships; Health; Families; Life Events; Wellbeing; Impact; Families and relationships; Health and wellbeing; Dsiadvantage, adversity and resilience; Adversity and resilience